(untitled) (Revista Lusófona de Educação, 2020)
This article inspects theory emerging from literature review and laboratory work on games for cultivating creative literacy. Whether games can or cannot instil or alienate one’s creativity is debatable. On one hand, they can be risk- and stress-free exploring grounds for people to interact in ways without parallel; on another, they can disengage players from the real world. Nevertheless, they have the potential to be turned into tools for thinking, for learning and for articulating knowledge between individuals. With that into consideration, we pinpointed two main groups that branch into four major categories: Behaviours – comprised of Attitudes and Competencies – and Conditions – comprised of Procedures and Resources – which we are structuring into a framework from which we draw hypotheses that undergo validation through play-testing sessions, in order to improve the framework. Keywords: creative literacy; games; play; game design.